Overcoming challenges in delivering integrated motivational interviewing and cognitive behavioural therapy for bipolar disorder with co-morbid alcohol use: therapist perspectives. Issue 5 (6th September 2020) - Berry, Katherine; Barrowclough, Christine; Fitsimmons, Mike; Hartwell, Rosalyn; Hilton, Claire; Riste, Lisa; Wilson, Ian; Jones, Steven
Abstract: Background: Alcohol misuse is common in bipolar disorder and is associated with worse outcomes. A recent study evaluated integrated motivational interviewing and cognitive behavioural therapy for bipolar disorder and alcohol misuse with promising results in terms of the feasibility of delivering the therapy and the acceptability to participants. Aims: Here we present the experiences of the therapists and supervisors from the trial to identify the key challenges in working with this client group and how these might be overcome. Method: Four therapists and two supervisors participated in a focus group. Topic guides for the group were informed by a summary of challenges and obstacles that each therapist had completed at the end of therapy for each individual client. The audio recording of the focus group was transcribed and data were analysed using thematic analysis. Results: We identified five themes: addressing alcohol use versus other problems; impact of bipolar disorder on therapy; importance of avoidance and overcoming it; fine balance in relation to shame and normalising use; and 'talking the talk' versus 'walking the walk'. Conclusions: Findings suggest that clients may be willing to explore motivations for using alcohol even if they are not ready to change their drinking, and they may want help with a range of mental health problems. Emotional and behavioural avoidance may be a key factor in maintaining alcohol use in this client group and therapists should be aware of a possible discrepancy between clients' intentions to reduce misuse and their actual behaviour.